2016
DOI: 10.1074/jbc.m116.735373
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wnt Signaling in Cortical Neurons Enhances Glucose Utilization through Glycolysis

Abstract: Edited by Jeffrey E. PessinThe Wnt signaling pathway is critical for a number of functions in the central nervous system, including regulation of the synaptic cleft structure and neuroprotection against injury. Deregulation of Wnt signaling has been associated with several brain pathologies, including Alzheimer's disease. In recent years, it has been suggested that the Wnt pathway might act as a central integrator of metabolic signals from peripheral organs to the brain, which would represent a new role for Wn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 100 publications
2
50
0
Order By: Relevance
“…The reaction was stopped by the addition of 10% trichloroacetic acid (TCA, cat: T6399), and the generation of NADPH was measured at 340 nm (Cisternas et al . ). All the reagents were purchased from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 97%
“…The reaction was stopped by the addition of 10% trichloroacetic acid (TCA, cat: T6399), and the generation of NADPH was measured at 340 nm (Cisternas et al . ). All the reagents were purchased from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 97%
“…In this regard, we have recently demonstrated that the loss of Wnt signalling favours the appearance of several pathological markers linked to AD in a wild-type murine model [102]. Moreover, we found that Wnt signalling is involved in the neuronal energy metabolism and that its activation rescues energy imbalance because of improved glucose utilisation [103]. On the other hand, Wnt signalling also plays a relevant role in PD.…”
Section: Wnt Signalling Pathwaymentioning
confidence: 82%
“…WNT3A is a Wnt ligand, activating The Wnt signaling pathway [21]. It has been reported that WNT3A is critical for The development and function of The nervous system [22], as well as for glucose metabolism in cortical neurons [23]. Thus, DTMUV may affect The development of nervous system through inhibition of WNT3A.…”
Section: Genes Related To Nervous Systemmentioning
confidence: 99%